Characterization of flavonoid derivatives from Boesenbergia Rotunda (L.) - Ching, Amy Yap Li; Tang , Sook Wah; Sukari, Mohd Aspollah; Lian, Gwendoline Ee Cheng; Rahmani, Mawardi; Khalid, Kaida (Malaysian Society of Analytical Sciences, 2007)
Three flavanones, pinostrobin (1), pinocembrin (2) and alpinetin (3) and two chalcones, cardamonin (4) and boesenbergin A (5) were isolated from the hexane and chloroform extracts of rhizomes of Boesenbergia rotunda (L.). The structures of all compounds were elucidated on the basis of spectroscopic data (IR, MS, and NMR) and 2-D NMR was carried out for the structure elucidation of boesenbergin A as a complementary to the spectroscopic data reported previously.